Knowing how we know: an epistemological rationale for the medical humanities. Issue 1 (January 2017) - Chiavaroli, Neville
Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss. Abstract : Context: Although their inclusion in medical curricula internationally is increasing, the medical humanities still face challenges to their role and place in the curriculum. Justifications supporting the inclusion of humanities content, methods and perspectives in medical curricula have generally been proposed along instrumental, intrinsic and critical lines. However, recent literature in the field has turned to 'ways of knowing' as representing an alternative, essentially epistemological, perspective on the matter. This involves the claim that the medical humanities align with and promote characteristic ways of understanding and practising medicine, which are not adequately represented in traditional disciplinary frameworks. Discussion: Such epistemological arguments aim to move beyond generic claims of medicine as both an 'art' and a 'science' to explore the way in which the humanities support the ultimate objectives of a medical education, particularly in relation to claims about requisite knowledge and typical reasoning. Not only can this help focus attempts to identify and document relevant learning or clinical outcomes, but it can potentially uncover evidence from education outcomes research which may not have been the focus of previous inquiry in the medical humanities and which may in fact be associated, at least in part, with curricular activities formally associated with humanities disciplines. Conclusions: An epistemological view of the humanities in medical education offers a significant new way of conceptualising and communicating the potential role of the humanities in medical training. If clinical practice can be characterised as rational but interpretive, partly predictable yet fundamentally uncertain, and logical but also intuitive, it follows that educational training should facilitate such ways of knowing and thinking. An epistemological perspective enables the argument that the medical humanities are valuable not because they are more 'humane', but because they help constitute what it means to think like a doctor.